EFEKTIVITAS PENERAPAN SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD) DALAM PERENCANAAN PEMBANGUNAN DI KOTA TOMOHON - Citta Nadya Celine Wurara; Stefanus Sampe; Donald K. Monintja; Michael Mamentu; Fanley N. Pangemanan; Steeva G. Rondonuwu (Halu Oleo University, 2024)
This research aims to analyze and determine the effectiveness of implementing the Regional Government Information System (SIPD) in development planning in Tomohon City. This research adopted a qualitative descriptive research method and was conducted at the Bappelitbangda office in Tomohon City, North Sulawesi. The data used in this research comes from primary and secondary data. The data analysis technique used interactive data analysis. The research results show the effectiveness of the Regional Government Information System (SIPD) application in development planning in Tomohon City, this application is considered innovative and able to increase the efficiency of planning preparation because it is electronic-based and integrated with the centre and regions. However, there are several obstacles that need to be taken into account, such as effectiveness indicators not yet being met due to frequently changing legal bases, lack of regular outreach and training for human resources, and limited infrastructure. Although this application is very helpful compared to manual methods, it still requires better adjustments and support in order to achieve optimal effectiveness according to Duncan's theory in Steers (2012).